1988
DOI: 10.3354/meps050161
|View full text |Cite
|
Sign up to set email alerts
|

Flux of ammonium from surf-zone and nearshore sediments in Nahant Bay, Massachusetts, USA, in relation to free-living Pilayella littoralis

Abstract: The availab~lity of inorganic nitrogen in the surf-zone of Nahant Bay, Massachusetts, USA, was studied in relation to the distribution and decomposition of a free-living population of the filamentous brown alga Pilayella littoralis. Slight ammonium enrichment was evident in the surf zone of one beach location and in the immediate vicinity of a sewage treatment plant outfall. Profiles of sediment ammonium were determined over an annual cycle at 4 mid-intertidal beach sites. Most sites contained sediment ammoniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In those studies, muddy sediments NH 4 + fluxes ranged from 72 nmol cm -2 d -1 to 127 nmol cm -2 d -1 whereas for HPO 4 2-, negative fluxes were determined pointing to sediment P-uptake. The present fluxes were also comparable with those found in other marine systems (Pregnall and Miller 1988;Lerat et al 1990;Kristensen 1993;Asmus et al 2000). Maximum NH 4 + exchange rates of 96 and 144 nmol cm -2 d -1 have been reported for marine environments in the coast of Ireland (Wilson and Brennan 2004).…”
Section: Discussionsupporting
confidence: 78%
“…In those studies, muddy sediments NH 4 + fluxes ranged from 72 nmol cm -2 d -1 to 127 nmol cm -2 d -1 whereas for HPO 4 2-, negative fluxes were determined pointing to sediment P-uptake. The present fluxes were also comparable with those found in other marine systems (Pregnall and Miller 1988;Lerat et al 1990;Kristensen 1993;Asmus et al 2000). Maximum NH 4 + exchange rates of 96 and 144 nmol cm -2 d -1 have been reported for marine environments in the coast of Ireland (Wilson and Brennan 2004).…”
Section: Discussionsupporting
confidence: 78%
“…At 1-or 2-m intervals inland from the waterline, narrow pits were dug to the water-saturation depth, where pore water began to pool in the bottom of the pit. Triplicate water samples were removed by syringe, filtered immediately (0.2 #m), and frozen until analysis (Pregnall and Miller 1988). Pore-water nutrients were determined on triplicate sediment cores (25 cm ~) taken 2 m seaward from the water line at water depths of 30 to 40 cm using tipless 30 cm 3 syringes.…”
Section: Study Areamentioning
confidence: 99%
“…Plants growing a few meters further offshore at only 0.4 m greater depth showed activity less than onetenth that of the shallow-edge plants. Although sandy beaches typically have little or no nitrate efflux (Nowicki and Nixon 1985, Asmus 1986, Pregnall and Miller 1988, Roth and Pregnall (l 988) postulated that input of nitrate via groundwater percolation might be responsible for the elevated NRA they observed in eelgrass plants growing at the shallow edge of the meadow just offshore of the beach.…”
Section: Introductionmentioning
confidence: 99%
“…Portugal O Inter-Research/Printed in Germany A literature review revealed that KC1 is commonly used to remove exchangeable NH,+ from marine sediments (Rosenfeld 1979, Blackburn 1980, Pregnall & Miller 1988, Lomstein et al 1990). However, there are variations in the use of the technique with regard to the degree of agitation (Terry & Nelson 1975, Haines et al 1977, Henriksen 1980, the molarity of KC1 solution (Bremner 1965, Sarrensen 1978, Blackburn & Henriksen 1983, Smith & Patrick 1983, the extraction period (Klingensmith & Alexander 1983, Jenkins & Kemp 1984, Simon & Kennedy 1987, Laima 1991, the extractant to sediment ratio (Laima unpubl.…”
Section: Introductionmentioning
confidence: 99%